2017
DOI: 10.1111/bjh.14580
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin reduces vaso‐occlusive pain in sickle cell anaemia: a pilot efficacy trial

Abstract: Summary Sickle cell anaemia (SCA) is a progressive vascular disease characterized by episodic vaso-occlusive pain. Despite the broad impact of inflammation on acute and chronic clinical manifestations of SCA, no directed anti-inflammatory therapies currently exist. Statins are cholesterol-lowering agents shown to confer protection from vascular injury by suppressing inflammation. We previously documented a reduction in soluble biomarkers of inflammation in patients with sickle cell disease treated with simvast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 88 publications
(124 reference statements)
1
39
0
Order By: Relevance
“…Although the effects of statins on the progression of kidney disease in human clinical trials remain controversial, studies have demonstrated significant improvement in proteinuria or albuminuria following treatment with statins as summarized in a recent meta‐analysis (Su et al , ). A small pilot study examining the effect of simvastatin in SCD patients found significant decreases in markers of inflammation and reduction in the frequency of pain episodes (Hoppe et al , ). In this study, treatment with simvastatin for 3 months resulted in decreased plasma levels of the endothelial marker soluble E‐selectin but not sVCAM‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of statins on the progression of kidney disease in human clinical trials remain controversial, studies have demonstrated significant improvement in proteinuria or albuminuria following treatment with statins as summarized in a recent meta‐analysis (Su et al , ). A small pilot study examining the effect of simvastatin in SCD patients found significant decreases in markers of inflammation and reduction in the frequency of pain episodes (Hoppe et al , ). In this study, treatment with simvastatin for 3 months resulted in decreased plasma levels of the endothelial marker soluble E‐selectin but not sVCAM‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Several new drugs with specific anti-inflammatory targets are currently in development. Anti-adhesion agents such as anti-E selectin (rivipansel, formerly GMI-1070), 17 anti-P selectin (crizanlizumab), 18 and broad anti-adhesives (simvastatin, AKT inhibitors), 19 used individually or in combination with hydroxyurea, have been shown to reduce VOEs. An opportunity now exists to further test new drugs in combination with hydroxyurea in order to potentiate the benefits provided by hydroxyurea therapy alone.…”
Section: Letters To the Editormentioning
confidence: 99%
“…Examples include, but are not limited to (1) the long‐term effects of hydroxyurea, hematopoietic stem cell transplantation, and transfusion therapy and the role of new interventions (e.g. anti‐inflammatory agents, Hb affinity modulators, anti‐oxidants, and gene therapy) in cumulative organ damage; (2) cognitive impairment, both its underlying mechanisms and the impact on social function; (3) the impact of the environment on the disease course, including poverty, which is prevalent in the SCD population; (4) pain control, particularly in patients who progress to chronic pain; (5) risk factors for bone mineral loss and osteonecrosis, including vitamin D deficiency, which is prevalent in SCD, and establishment of prevention and treatment guidelines; (6) risk factors for sickle nephropathy in older children and adults and the role of renal‐modifying therapies; (7) factors underlying the sharp increase in mortality in young adults, as compared to children; and (8) how biomarkers can be used to monitor treatment response and disease severity …”
Section: Discussionmentioning
confidence: 99%
“…SCCRIP participants have raised no significant concerns regarding the use of their biospecimens for future genetic studies, and most cite possibly contributing to the development of curative therapies as a motivation for study participation. Hb affinity modulators, [70][71][72] anti-oxidants, 73 and gene therapy 74 how biomarkers can be used to monitor treatment response and disease severity. 76 A major long-term goal of SCCRIP is to utilize genomic studies to predict SCD outcomes and guide treatment.…”
Section: Discussionmentioning
confidence: 99%